(untitled) (Journal of Economic Research & Business Administration, 2021)
Sequel to the paucity of government revenue to fulfill fiscal responsibilities because of downplayed oil revenue from world market, Nigeria government invariably veered to nonoil taxation as a pertinent source of revenue to actualize government expenditure. Therefore, this study appraised nonoil taxation effect on government expenditure from 1981 to 2019 in Nigeria. This study further assessed the bearing of causality amid Government Expenditure, Value Added Tax, Company Income Tax, Custom and Excise Duties and Education Tax, enthusiastically hiring VECM, Johansen co-integration, Units root, and Granger causality tests. Outcomes bared that Value Added Tax has positive significant effect on Government Expenditure. Furthermore, Value Added Tax granger- cause government Expenditure, also government Expenditure granger- cause Value Added Tax. It is also exposed that Company Income Tax had long run and short run positive significant outcome on government Expenditure. More so, Custom and Excise Duties and Education Tax upsurges government Expenditure positively and significantly. Conclusively, nonoil taxation enhanced government expenditure positively, strongly and significantly. This revealed that economic benefits that accrued from nonoil taxation income have effectively expended on government expenditure in terms of fulfilling both the current and capital expenditure as expected. It is advocated that government should expedite more nonoil taxes collection devices to avail more income which can be empathically, judiciously, effectively and prudently expended on government expenditure for more anticipated civil responsibilities from the populace. Key words: Value Added Tax, Custom and Excise Duties, Education Tax, Company Income Tax, Government Expenditure.